Low Z‐4OHtam concentrations are associated with adverse clinical outcome among early stage premenopausal breast cancer patients treated with adjuvant tamoxifen. Issue 4 (14th December 2020) - Helland, Thomas; Naume, Bjørn; Hustad, Steinar; Bifulco, Ersilia; Kvaløy, Jan Terje; Sætersdal, Anna Barbro; Synnestvedt, Marit; Lende, Tone Hoel; Gilje, Bjørnar; Mjaaland, Ingvil; Weyde, Kjetil; Blix, Egil Støre; et al.
Abstract : Low steady‐state levels of active tamoxifen metabolites have been associated with inferior treatment outcomes. In this retrospective analysis of 406 estrogen receptor‐positive breast cancer (BC) patients receiving adjuvant tamoxifen as initial treatment, we have associated our previously reported thresholds for the two active metabolites, Z‐endoxifen and Z‐4‐hydroxy‐tamoxifen (Z‐4OHtam), with treatment outcomes in an independent cohort of BC patients. Among all patients, metabolite levels did not affect survival. However, in the premenopausal subgroup receiving tamoxifen alone ( n  = 191) we confirmed an inferior BC ‐specific survival in patients with the previously described serum concentration threshold of Z‐4OHtam ≤ 3.26 nm (HR = 2.37, 95% CI = 1.02–5.48, P  = 0.039). The 'dose–response' survival trend in patients categorized to ordinal concentration cut‐points of Z‐4OHtamoxifen (≤ 3.26, 3.27–8.13, > 8.13 nm ) was also replicated ( P ‐trend log‐rank = 0.048). Z‐endoxifen was not associated with outcome. This is the first study to confirm the association between a published active tamoxifen metabolite threshold and BC outcome in an independent patient cohort. Premenopausal patients receiving 5‐year of tamoxifen alone may benefit from therapeutic drug monitoring to ensure tamoxifen effectiveness. Abstract : Concentrations of active tamoxifen metabolites may be predictive of tamoxifen efficacy, and several therapeutic thresholds have been reported. This study of 406 ER+ breast cancer patients replicated an association between a previously reported active tamoxifen threshold (Z‐4OHtam ≤ 3.26 nm ) and adverse BC outcome. The association was identified in early‐stage premenopausal patients using tamoxifen alone without sequential aromatase inhibitor use.